Enhancing quality of experience (QoE) in IM-Tahfiz framework for predictive acceptance influence of user screening test - Mohammad Fahmi Abdul Hamid,; Muhamad Hanif Jofri,; Nor Adina Abdul Kadir,; Khairul Azhar Meerengani,; Muhammad Taufik Md Sharipp,; Salahuddin Suyurno, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Tahfiz teaching has become progressively more conventional and is growing as an essential educational course. This significance is in line with the prospect above that is placed on the ability of tahfiz schools to produce Quran memorising students who can thrive and improve the nation’s Islamic education. Due to this endeavour, the tahfiz learning management process must satisfy the user QoE related to the increasing student intake issues. These issues impact this education process due to insufficient tahfiz resources, infrastructure, and facilities. This paper proposes the Integrated Management Tahfiz (IM-Tahfiz) Framework’s suitability for selected education satisfaction at the empirical level. The primary purpose of this framework is about the Quality of Experience (QoE) based on user satisfaction for the screening test of stakeholder decision in selecting tahfiz centre to educate students. This framework design was implemented in three phases; data selection, where instruments and experiment setup gather resources from the mobile to the server to finalize data; user QoE setup, where the users’ data is obtained by using the Mean Opinion Score (MOS) to determine this matter’s solution regarding the suitability of tahfiz students to tahfiz centers; and execution phase, where both phases combine to finalize the data output. The final result illustrates the initial research question (RQ) was the factor that had effects on the problem of the tahfiz center that can be solved accordingly.